Kształcenie studentów z niepełnosprawnością jako wyraz społecznej odpowiedzialności uniwersytetu - Skalska, Katarzyna (Rocznik Pedagogiczny, 2022)
The purpose of this article is to describe the universities’ social responsibility in the context of educating students with disabilities. In Poland, mass education of students with disabilities is a phenomenon that has been going on for about two decades. The first activities of the universities focused mainly on removing architectural barriers, as well as raising awareness of the institution’s employees in terms of the needs of students with various types of disabilities. However, nowadays, we can consider not only possibilities of implementing the education processes by this group of students, but also the prospects of realizing their subjectivity and autonomy in the academic environment. The article presents chosen (relevant to its purpose) research results in the field of functioning of students with disabilities in the academic environment.